The Pursuit of Elena Bradford - Gabhart, Ann H., 1947- (Thorndike, Maine : Center Point Large Print, 2025)
"At twenty-two, Elena Bradford has never met a man who made her consider marriage. But when her father dies and leaves the family deeply in debt, Elena becomes her familys only hope. Her mother uses their last funds to take Elena and her younger sister to Graham Springs, Kentucky, where people find healing by drinking the mineral spring water and healthy recreation through the many daily activities -- including dances almost every evening. As her mother schemes to find Elena a wealthy husband, Elena finds herself drawn to two men her mother would never consider. Charming artist Kirby Frazier spends his days drawing and painting the guests, but his real mission is to find a wealthy bride to finance his dream to go west. Melancholy Andrew Harper has come to Graham Springs in need of healing after a broken heart. When a beautiful young lady shows up at the Springs with no chaperone and a story that seems suspicious, nearly everyone is charmed and intrigued. But when an unexpected tragedy occurs, Elena, Kirby, and Andrew will all be faced with decisions of life, love, and loyalty."--
Keywords: Single women -- Fiction; Marriage -- Economic aspects; Fiction; Man-woman relationships -- Fiction; Triangles (Interpersonal relations) -- Fiction; Health resorts -- Kentucky; Fiction; Kentucky -- History -- 1792-1865; Fiction; Christian fiction; Romance fiction; Historical fiction; Large print books